Electrical Performance of Epoxy Resin Filled with Micro Particles and Nanoparticles. (March 2017) - Liang, Mu; Wong, K.L.
Abstract: Composite insulators are widely used in the overhead transmission system. Compared with porcelain products, composite has many advantages such as light in weight, hydrophobicity characteristic and superior mechanical property. However, composite products are also suffering from issues such as low tracking resistance and early failures. The use of nano or micro fillers is considered to be one of the methods that can further improve the properties of the composite product. This study is aimed to study the electrical properties of nano and micro filled epoxy resin. SiO2 and Al2 O3 nano and micro fillers are used in this research for comparison purposes. The host matrix, which is epoxy resin, is filled with nano particles, micro particles or both nano and micro particles. Micro particles and nano particles are dispersed into epoxy resin using planetary centrifugal mixing technique and degassed in vacuum. In total, seven types of materials are prepared in this study. These materials are (1) neat epoxy, (2) nanocomposite filled with 1 wt% nano SiO2 fillers, (3) micro-composite filled with 20 wt% micro SiO2 fillers, (4) micro-nano composite filled with 1 wt% nano SiO2 and 20 wt% micro SiO2 fillers, (5) nanocomposite filled with 1 wt% nano Al2 O3 fillers, (6) micro-composite filled with 20 wt% micro Al2 O3 fillers, (7) micro-nano composite filled with 1 wt% nano Al2 O3 and 20 wt% micro Al2 O3 fillers. In this study, AC electrical breakdown strength test are performed using a sphere-to-sphere setup. The thickness of all the samples is 1 mm ± 0.1 mm in accordance to the IEC standard. Surface partial discharge measurement is also performed to evaluate the surface property.